(untitled) (Theoretical and Applied Linguistics@ro, 2025)
Francisco Yus, professor at the University of Alicante, Spain, is one of the founders of cyberpragmatics (Yus 2010, 2011) and a leading scholar in media pragmatics (Yus 2017a). His constant research interests revolve around the Theory of Relevance (Sperber, Wilson 1995, and subsequent studies), which he applied to various conversational phenomena such as irony and humour (Yus 2023, 2024), multimodality (Yus 2018), misunderstandings (Yus 1999), and to various online discourse (sub)genres generated in chat rooms (Yus 2005), on Facebook (Yus 2014a), WhatsApp (Yus 2017b), and smartphones (Yus 2021), among others. In his recent book, the author puts at work his extensive readings, intuitions, expertise, and creative interpretations, his keen sense of observation and analytic skills to provide the reader with a deep understanding of the functioning of emojis in cyberspace.